PROBLEMS AND STRATEGIES OF LEARNING THE QUR'AN IN SCHOOLS: A COMPARATIVE ANALYSIS BETWEEN PUBLIC SCHOOLS AND ISLAMIC-BASED SCHOOLS - Puput Rahmania; Agus Fakhruddin; Ganjar Eka Subakti (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimsed to explore the fundamental problems encountered by teachers in teaching the Qur’an and to analyze these problematics through an integrative theoretical perspective. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews with ten Islamic Religious Education teachers from elementary, junior high, and senior high schools in Bandung, Indonesia. The findings reveal several persistented problematics, including limited instructional time, students’ low initial ability to read the Qur’an, minimal parental involvement, heterogeneous student backgrounds, as well as weak student motivation and self-confidence. These problematics indicated that Qur’anic learning is influenced not only by classroom pedagogy but also by broader environmental, social, and psychological factors. Drawing on Bronfenbrenner’s Ecological Systems Theory, Bandura’s Social Learning Theory, and Self-Determination Theory, this study demonstrated that difficulties in Qur’anic learning emerge from complex interactions among family environments, social modeling processes, and students’ basic psychological needs. The implications of this study emphasized the need for holistic and ecosystem-based instructional strategies that strengthen home–school collaboration, provide observable role models, and support students’ motivation and self-confidence in learning the Qur’an. These findings offered valuable insights for teachers, school leaders, and policymakers in improving the quality of Qur’anic instruction in formal education